ADJECTIVE SUFFIXES IN THE HATE U GIVE NOVEL: ITS FORMS AND QUANTITIES - Winarna; Riska Dwi Aprilia (Bajang Institute, 2022)
: This study aims to classify and describe the types of suffixes used to form adjectives found in novel titled The Hate U Give, determine the meanings indicated by the process as well as the number of uses of adjective-forming suffixes in the novel. The data source of this study were taken from the novel. This study used descriptive qualitative method to analyze the data. The theory used in analyzing data is the derivational suffixes theory by Plag (2001). This theory explains the formation of words, especially the derivational suffixes forming adjectives. The second theory in analyzing data is the types of meanings indicated by the process of derivational suffixes forming adjectives by Leech (1974). The results showed that there are twelve types of suffixes that make up the adjectives used in the novel, they are; 'suffix-able', 'suffix-ful', 'suffix-ic', 'suffix-ish', 'suffix-ive', 'suffix-ous', 'suffix-ible', 'suffix-ing', 'suffix-less', 'suffix-y', 'suffix-ed', and 'suffix-ly'. The suffix function that makes up an adjective is to modify the meaning of the base word. The base word will undergo a class change of words to adjectives after the suffix ending is added. Based on the results of the study, 'suffix-y' is a type of suffix that forms the most commonly used adjectives.